Plasmonics: Magnetic Plasmonic Fano Resonance at Optical Frequency (Small 18/2015). Issue 18 (May 2015) - Bao, Yanjun; Hu, Zhijian; Li, Ziwei; Zhu, Xing; Fang, Zheyu
<x xml:space="preserve">Abstract</x> Single and double circular split ring hexamers are reported by Z. Fang and co‐workers on page 2177 to suppress the radiation loss of plasmonic Fano resonance. With the illumination of azimuthally polarized light, the interference between a broad collective magnetic mode and a dark magnetic mode within each split ring generates a pure magnetic Fano resonance. The suggested configuration with narrower line‐shape magnetic Fano resonance has significant applications in low‐loss sensing and may serve as an elementary building block for optical metamaterials.